2023
DOI: 10.1038/s41598-023-31977-y
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary lifestyle with increased risk of obesity in urban adult academic professionals: an epidemiological study in West Bengal, India

Abstract: Ectopic fat deposition is more strongly associated with obesity-related health problems including type 2 diabetes mellitus (T2DM), cardiovascular diseases (CVD), hypothyroidism, arthritis, etc. Our study aimed at identifying the cumulative role of several risk factors in developing obesity and the role of ectopic fat (visceral fat) in predicting cardiovascular disease risk in varied age groups among urban adult academic professionals in West Bengal. 650 adults (Male = 456; Female = 194) associated with the aca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Kurang aktivitas fisik dan pola hidup sedentari merupakan faktor risiko obesitas [5]. Namun, kelebihan berat badan dan obesitas juga merupakan faktor risiko kurang aktivitas fisik dan pola hidup sedentari [6,7]. Orang obesitas kurang aktif dan menghabiskan lebih sedikit energi untuk aktivitas fisik daripada orang dengan berat badan yang lebih ringan [6].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kurang aktivitas fisik dan pola hidup sedentari merupakan faktor risiko obesitas [5]. Namun, kelebihan berat badan dan obesitas juga merupakan faktor risiko kurang aktivitas fisik dan pola hidup sedentari [6,7]. Orang obesitas kurang aktif dan menghabiskan lebih sedikit energi untuk aktivitas fisik daripada orang dengan berat badan yang lebih ringan [6].…”
Section: Pendahuluanunclassified
“…Kedua komponen tersebut memang membentuk lingkaran setan. Berbagai penelitian lain di dunia juga melaporkan bahwa obesitas merupakan faktor risiko penurunan aktivitas fisik sementara penurunan aktivitas fisik merupakan faktor risiko obesitas [7,10].…”
Section: Rst -T N (%) Status Giziunclassified
“…The prevalence of obesity is intricately linked to contemporary lifestyle habits, characterized by a Western diet, sedentary living, and a decline in physical activity. These factors contribute significantly to the rise in metabolic disorders, including atherosclerosis and non-alcoholic fatty liver disease (NAFLD) [ 1 - 3 ]. According to a review paper by Philipp Kasper et al, the global prevalences of NAFLD and nonalcoholic steatohepatitis (NASH) are approximately 25% and 5% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence represents a critical period of transition from child to adult health care, but readiness for this transition has been described as low in the general adolescent population (Mulkey et al, 2023). The increase in obesity is known to become the highest rate in early adulthood (Ghosh et al, 2023;GBD 2015Obesity Collaborators, 2017. Globally, the prevalence of obesity aged ≥18 years has increased almost threefold since 1975 reaching 4.7% until 2016 reaching 13% of the world's population (11% of men and 15% of women) (WHO, 2021).…”
mentioning
confidence: 99%
“…Globally, the prevalence of obesity aged ≥18 years has increased almost threefold since 1975 reaching 4.7% until 2016 reaching 13% of the world's population (11% of men and 15% of women) (WHO, 2021). Recent studies have shown that South Asian populations have a higher tendency to develop obesityrelated non-communicable diseases compared to Caucasians (Ghosh et al, 2023). Obesity and overweight in adolescence are associated with a range of short-and long-term consequences, including adverse direct effects on physical and psychological health and a significantly increased risk of obesity and adverse health outcomes in adulthood (Moore Heslin et al, 2023).…”
mentioning
confidence: 99%